PELATIHAN PEMBUATAN STIK DENGAN MEMANFAATKAN KULIT BUAH NAGA DI KALURAHAN MARGOSARI - Munif, Ngabdul (Jurnal Abdimas Akademika, 2023)
The objectives of this community service activity are: (1) provide knowledge in processing dragon fruit peel waste, (2) provide skills in making and packaging dragon fruit peel stick products, (3) provide knowledge and skills related to calculating the selling price of dragon fruit peel stick products. The methods used include lectures, demonstrations, questions and answers and mentoring. The results of the service showed that: (1) participants have knowledge in processing dragon fruit peel waste, (2) participants have skills in making and packaging dragon fruit peel stick products, (3) participants have knowledge and skills related to calculating the selling price of dragon fruit peel stick products. Further service recommendations can be taken regarding training in making e commerce platforms to increase sales in the digital era.